Pengaruh Penambahab Sari Buah Lemon Terhadap Tekstur dan Warna Pada Yoghurt Susu Kambing - Riki Aprianto; Supranoto Supranoto; Wida Nurnaningsih; Tri Sukmaningsih (MEDIA PETERNAKAN, 2025)
The research titled "The Effect of Lemon Juice Addition on Texture and Color of Goat Milk Yogurt" was conducted at the Laboratory of the Faculty of Animal Husbandry, Wijayakusuma University, Purwokerto, on June 26-27, 2024. The materials used in this study included 1000 ml of goat milk, 50 ml of yogurt starter, and 63 ml of lemon juice. The research method used was experimental with a Completely Randomized Design (CRD) in a one-way pattern. This study consisted of 4 treatments and 25 replications, with the treatments including P0 (no lemon juice addition), P1 (1% lemon juice addition from the total yogurt mixture volume), P2 (2% lemon juice addition from the total yogurt mixture volume), and P3 (3% lemon juice addition from the total yogurt mixture volume). The variables observed were organoleptic tests for texture and color, conducted by 25 semi-trained panelists. The data were analyzed using variance analysis followed by the Least Significant Difference (LSD) test. The results showed that the addition of lemon juice had a very significant effect (P<0.01) on the texture and color of goat milk yogurt.